Crystalline lens imaging with a slit-scanning system - Oliveira, Cristina (2011)
[Introduction] The human crystalline lens plays a fundamental role on the retinal image quality. The ability of the lens to change its shape and, consequently, the total refractive power of the eye, during accommodation, enables one to focus objects at a wide range of distances. Knowledge regarding the crystalline lens’ geometric properties provides insights into the focusing mechanism of the visual system. Namely, the study of changes in surface shape and curvatures of the lens during accommodation is essential for a better understanding of the accommodation mechanism itself [1,2]; the age-related changes in these geometric properties of the lens are necessary to explain the etiology and progression of presbyopia [3,4]. Furthermore, crystalline lens’ optical properties, such as focal length and spherical aberrations, are closely related to its geometric properties. The aim of this work is to present a slit-scanning tomography system that’s capable of imaging the anterior chamber of the eye. We overview the applicability of our device to the crystalline lens.